2021
DOI: 10.52964/amja.0853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic vasoconstriction and prognosis using thermography: a systematic review

Abstract: Purpose: This systematic review investigates whether infrared thermography (IRT) can measure systemic vasoconstriction and addresses the value of IRT in assessing circulatory deficiency and prognoses. Methods: Design was based on the PRISMA criteria and a systematic search of 6 databases was performed. Results: Of 3,198 records, five articles were included. Three clinical studies were identified; two found significant correlations between IRT obtained temperatures and mortality. An experimental study found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…International Acute Medicine colleagues from Denmark and Hong Kong present some innovative work on the potential use of thermography in predicting prognosis in acute care. 2 In a prospective study of 726 patients they demonstrated that the temperature gradient between nose and eye could help identify variations in skin perfusion and was predictive Evolve, Adapt, Innovate and Deliver: Acute Medicine post COVID pandemic of all cause 30 day mortality. 3 This requires further study but may become a further useful tool in the assessment of physiology of acute unwell medical patients.…”
Section: Editorialmentioning
confidence: 99%
“…International Acute Medicine colleagues from Denmark and Hong Kong present some innovative work on the potential use of thermography in predicting prognosis in acute care. 2 In a prospective study of 726 patients they demonstrated that the temperature gradient between nose and eye could help identify variations in skin perfusion and was predictive Evolve, Adapt, Innovate and Deliver: Acute Medicine post COVID pandemic of all cause 30 day mortality. 3 This requires further study but may become a further useful tool in the assessment of physiology of acute unwell medical patients.…”
Section: Editorialmentioning
confidence: 99%